1998
DOI: 10.21273/horttech.8.4.590
|View full text |Cite
|
Sign up to set email alerts
|

Using Commercial Bumble Bee Colonies as Backup Pollinators for Honey Bees to Produce Cucumbers and Watermelons

Abstract: The effectiveness of bumble bees, Bombus impatiens Cresson, and honey bees, Apis mellifera L., on the pollination of cucumber, Cucumis sativus L., and watermelon, Citrullus lanatus (Thunb.) Matsum. & Nakai, was compared under field conditions. Comparisons were based on fruit abortion rates and seed set as influenced by bee type (honey bee or bumble bee) and the number of bee visits to treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 0 publications
1
16
0
2
Order By: Relevance
“…Thus, Tepedino (1981) showed that single bee visits were rarely sufÞcient to fully pollinate a zucchini ßower (also C. pepo), but a second ßoral visit from a female Peponapis or a honey bee could substantially improve fruit growth. Additional ßoral visits by bees were also reported to improve pollination and fruiting at pumpkin (C. pepo) (Jaycox et al 1975), cucumber (Cucumis sativus L.), and watermelon (Citrullus lanatus L.) (Stanghellini et al 1998). Fruit abortion became negligible and seed set maximal when ßowers of these latter crops receive 12 or more visits from managed bumblebees or honey bees.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Tepedino (1981) showed that single bee visits were rarely sufÞcient to fully pollinate a zucchini ßower (also C. pepo), but a second ßoral visit from a female Peponapis or a honey bee could substantially improve fruit growth. Additional ßoral visits by bees were also reported to improve pollination and fruiting at pumpkin (C. pepo) (Jaycox et al 1975), cucumber (Cucumis sativus L.), and watermelon (Citrullus lanatus L.) (Stanghellini et al 1998). Fruit abortion became negligible and seed set maximal when ßowers of these latter crops receive 12 or more visits from managed bumblebees or honey bees.…”
Section: Discussionmentioning
confidence: 99%
“…But bumblebees have clear advantages over honeybees in some selected crops. Partly because of their extended "tongue" anatomy, bumblebees may actually be superior, overall, to honeybees for Downloaded by [Northeastern University] at 23:41 04 January 2015 cranberries, red clover, alfalfa (Holm 1966), watermelons, and cucumbers (Stanghellini, Ambrose, and Schultheis 1998); even though there are actually lesser-known crop-specific bees that do an even better job on some of these crops, which will be discussed below.…”
Section: Bumblebeesmentioning
confidence: 99%
“…For the past seven years, we have been evaluating the potential of commercial bumble bee (Bombus impatiens Cresson) colonies as alternative pollinators for honey bees on selected vine crops (Stanghellini et al, 1997(Stanghellini et al, , 1998a(Stanghellini et al, , 1998b(Stanghellini et al, , 2002. As an adjunct to this research, we were afforded the opportunity to investigate pollen mobilization on these crops.…”
mentioning
confidence: 99%